1997
DOI: 10.1006/dbio.1996.8500
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Planar and Early Vertical Signaling in Patterning the Expression ofHoxb-1inXenopus

Abstract: In this paper we examine the contributions of planar and vertical signaling to the patterning of gene expression in neural development and we examine the routes of this neural induction. We have examined how the expression of Xenopus homeobox gene, Hoxb-1, is regulated by instruction from the mesoderm and/or endoderm and ask whether this instruction is by the vertical or planar routes. We investigated normal expression patterns of Hoxb-1 during early Xenopus development and Hoxb-1 expression in sandwich explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…3H). However, in contrast to intact embryos, no XF expression is seen along the extended neural axis of these explants, which lack a floorplate under these culture conditions (Poznanski and Keller, 1997).…”
Section: Xenopus Fibrillin Is Expressed Specifically In Dorsal Involumentioning
confidence: 70%
“…3H). However, in contrast to intact embryos, no XF expression is seen along the extended neural axis of these explants, which lack a floorplate under these culture conditions (Poznanski and Keller, 1997).…”
Section: Xenopus Fibrillin Is Expressed Specifically In Dorsal Involumentioning
confidence: 70%
“…3A). This device measures the cumulative tensional convergence forces developed by pairs of control or morphant marginal zone explants in a 'giant sandwich' configuration (Sater et al, 1993;Poznanski and Keller, 1997). We found that explants derived from RLC morphant embryos converged with about 500 nN less force than control explants by the end of gastrulation (Fig.…”
Section: Rlc Phosphorylation Is Required To Generate Convergence Forcmentioning
confidence: 88%
“…Pattern formation and cell fate determination have been studied intensively in a number of eukaryotic organisms (7,9,11,12,15). Competition and lateral inhibition among equivalent cell groups are common themes underlying the mechanisms of pattern formation and organogenesis (18).…”
Section: Discussionmentioning
confidence: 99%